The great Flamarion - Mann, Anthony, 1906-1967; Von Stroheim, Erich, 1885-1957; Hughes, Mary Beth, 1919-1995; Republic Pictures Corporation; Cinetel Films ([Hollywood, CA] : Republic Picture : T-V Pic, Inc., 1945)
The romantic triangle between vaudeville performer The great Flamarion and his two assistants leads to betrayal and murder.
"Story by Anne Wigton based on a character "Big Shot" by Vicki Baum from Collier's.
Eric von Stroheim, Mary Beth Hughes, Dan Duryea, Stephan Barclay, Lester Allen, Esther Howard, Michael Mark.
Photography, Jaes S. Brown Jr.; editor, John F. Link; music, Alexander Laszlo.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 9, 2015)
Keywords: Vaudeville -- Drama; Shooters of firearms -- Drama; Americans -- Mexico -- Mexico City -- Drama; Popular music -- United States -- 1941-1950.; Man-woman relationships -- Drama; Feature films; Crime films; Film noir; Internet videos; Streaming video